CHILD LABOR AND ITS IMPACT ON SOCIETY; A SOCIOLOGICAL STUDY OF DISTRICT MALIR, KARACHI - Zuberi, Maryam; Ali, Mumtaz; Saeed, Naima (PEOPLE: International Journal of Social Sciences, 2020)
In our daily life we see many children under the age of 14 working on the streets, which is school going age, but due to lack of resources, huge family size, illiteracy, poverty and other reason they are compel to work rather than going school. The purpose of the research was to determine the status of child labor in District Malir. Study shows out that most of the children belong to Sindhi and Balochi ethnic group. Majority of children were boys. Majority of the children were illiterate and belong to those families where their parents are labor, disable, drug addicted, bagger, unemployed and elderly. In few cases the children were orphans and they didn’t have any other source of income that’s why they were compelled to do their work and play the part of bread winner for their families. Due to working environment and working hour these children don’t have the time for playing game and other physical healthy activities. Not only government but also different NGO’s are working for the welfare of these children at the national level. Overall scenario shows children are in bad condition. Education is the crucial need that should be considered.